2011
DOI: 10.1007/s00182-011-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

Pure strategy equilibria in symmetric two-player zero-sum games

Abstract: We observe that a symmetric two-player zero-sum game has a pure strategy equilibrium if and only if it is not a generalized rock-paper-scissors matrix. Moreover, we show that every finite symmetric quasiconcave two-player zero-sum game has a pure equilibrium. Further sufficient conditions for existence are provided. Our findings extend to general two-player zero-sum games using the symmetrization of zero-sum games due to von Neumann. We point out that the class of symmetric twoplayer zero-sum games coincides w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…I have showed that two-person symmetric zerosum games that possess this property have at least one equilibrium in pure strategies. Furthermore, this concept generalizes both generalized ordinal potentials (Monderer and Shapley, 1996) and quasiconcavity (Duersch et al, 2012a). Optimin equilibrium: An extension of maximin strategies…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…I have showed that two-person symmetric zerosum games that possess this property have at least one equilibrium in pure strategies. Furthermore, this concept generalizes both generalized ordinal potentials (Monderer and Shapley, 1996) and quasiconcavity (Duersch et al, 2012a). Optimin equilibrium: An extension of maximin strategies…”
Section: Resultsmentioning
confidence: 99%
“…In this chapter, I will introduce three sufficient conditions for the existence of a pure Nash equilibrium in two-person symmetric zero-sum games: (1) a quasiconcavity notion based on the preferences of a decision maker in the equivalent decision problem of a game; (2) a functional representation of an axiom in Fishburn and Rosenthal (1986); (3) the so-called sign-quasiconcavity notion, which is a generalization of quasiconcavity in Duersch et al (2012a).…”
Section: Chaptermentioning
confidence: 99%
See 3 more Smart Citations